1976
DOI: 10.1016/0035-9203(76)90009-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Mediterranean leishmaniasis IV. The leishmanin skin test in cutaneous leishmaniasis

Abstract: The leishmanin skin test was used in four different areas of the Italian Adriatic coast (Emilia Romagna, Marche, San Marino and Abruzzi), old endemic areas for cutaneous leishmaniasis. The test was found to be postitive in 80% of past infections, the 20% negative reactions being found in those who had been infected 20 or more years before. In the old endemic area of Teramo there was increasing positivity with age, with a sharp rise in the over 30 years age group suggesting that there had been a sudden break in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 4 publications
5
24
0
1
Order By: Relevance
“…The documentation of positive leishmanin skin tests (evidence of delayed antileishmanial hypersensivity), with no history of VL, is not new [3][4][5].…”
Section: Introductionmentioning
confidence: 98%
“…The documentation of positive leishmanin skin tests (evidence of delayed antileishmanial hypersensivity), with no history of VL, is not new [3][4][5].…”
Section: Introductionmentioning
confidence: 98%
“…Second, in the absence of public health surveillance at the European level, underreporting is common (see the Leishmaniasis and the Globalization of Neglect section). Third, asymptomatic infections may be common in some regions: for 1 clinical case of VL, there may be 30-100 subclinical infections (12). This underreporting can have major consequences for blood banks: blood from donors living in areas of endemicity in southern France and Greece had 3.4% and 15% seropositivity, respectively (13,14).…”
Section: Leishmaniasis In Europementioning
confidence: 99%
“…Even though it was reported that both pathogens could be transmitted through sharing of needles among intravenous drug users (34), in many cases of co-infection, the parasite was already present at the time of HIV infection, which indicates that HIV infection would have an unmasking effect on the true endemicity of Leishmania infection. In other words, the wave of Leishmania/HIV co-infection showed that L. infantum could behave as an opportunistic parasite, with many asymptomatic carriers (12), and with the clinical syndromes being only the tip of the iceberg. Because of the highly active antiretroviral therapy, cases of co-infection generally decreased in the region, with the exception of Portugal (35).…”
Section: Leishmaniasis and The Globalization Of Neglectmentioning
confidence: 99%
“…First, the prevalence of the AI profile increased with age. Although this may be interpreted as clear evidence that delayed hypersensitivity 6,13,26,1 (acquired cellular immunity) increases with age , in fact it only reflects the fact that that older individuals (³ 21 years of age) have had a longer exposure than younger individuals (1-10 and 11-20 years of age). In contrast, the incidence of the AI profile decreased with age, with a significant reduction of the number of cases from the two youngest groups (1-10 and 11-20 years of age: 30 cases each, 44.8%) to the oldest one (³ 21 years: seven cases, 10.4%).…”
Section: Discussionmentioning
confidence: 99%